The biological function of the type II toxin-antitoxin system ccdAB in recurrent urinary tract infections - Zhang, He; Tao, Shuan; Chen, Huimin; Fang, Yewei; Xu, Yao; Chen, Luyan; Ma, Fang; Liang, Wei (Frontiers in Microbiology, 2024)
Urinary tract infections (UTIs) represent a significant challenge in clinical practice, with recurrent forms (rUTIs) posing a continual threat to patient health. Escherichia coli (E. coli) is the primary culprit in a vast majority of UTIs, both community-acquired and hospital-acquired, underscoring its clinical importance. Among different mediators of pathogenesis, toxin-antitoxin (TA) systems are emerging as the most prominent. The type II TA system, prevalent in prokaryotes, emerges as a critical player in stress response, biofilm formation, and cell dormancy. ccdAB, the first identified type II TA module, is renowned for maintaining plasmid stability. This paper aims to unravel the physiological role of the ccdAB in rUTIs caused by E. coli, delving into bacterial characteristics crucial for understanding and managing this disease. We investigated UPEC-induced rUTIs, examining changes in type II TA distribution and number, phylogenetic distribution, and Multi-Locus Sequence Typing (MLST) using polymerase chain reaction (PCR). Furthermore, our findings revealed that the induction of ccdB expression in E. coli BL21 (DE3) inhibited bacterial growth, observed that the expression of both ccdAB and ccdB in E. coli BL21 (DE3) led to an increase in biofilm formation, and confirmed that ccdAB plays a role in the development of persistent bacteria in urinary tract infections. Our findings could pave the way for novel therapeutic approaches targeting these systems, potentially reducing the prevalence of rUTIs. Through this investigation, we hope to contribute significantly to the global effort to combat the persistent challenge of rUTIs.